Pelatihan penggunaan Aplikasi Mendeley untuk meningkatkan kualitas penulisan akademik mahasiswa - Pramudya, Febri Nur; Rizal, Abdul; Ginting, Nina Maksimiliana; Prisdinawati, Dwita; Yanuarti, Mira; Novianti, Maya (Nur Science Institute, 2025)
The training on the use of the Mendeley application was carried out as an effort to improve students’ skills in academic writing. Many students still performed citation and bibliography preparation manually, which often led to errors and inconsistencies. This community service activity applied a participatory training method based on hands-on practice, consisting of interactive lectures, technical demonstrations, and independent practice with guidance. The participants were 14 final-year students who were taking the Research Methodology course or writing their undergraduate thesis. The evaluation results indicated a significant improvement in students’ skills, where the average mastery, initially below 25%, increased to more than 80% after the training. In addition, the writing practice results showed that students were able to use Mendeley to import references, generate automatic citations, and create bibliographies. Therefore, this training proved effective in enhancing students’ digital literacy, supporting academic integrity, and can be replicated in other universities.